Olympia 2. Teil - Fest der Schönheit - Riefenstahl, Leni (Germany, 1938)
The second part of Leni Riefenstahl's famous documentary of the 1936 Berlin Olympic Games. The film captures the grace of athletes during field hockey, soccer, bicycling, equestrian, aquatic and gymnastic events. Highlights are the Pentathlon and the Decathlon, which was won by American Glenn Morris. It ends with the triumphant conclusion of the games.
Keywords: Documentary films